New insights into Cortinarius: Novel taxa from subtropical China - Meng-Le Xie; Yong Yu; Pan Long; Zuo-Hong Chen; Zi-Rui Wang; Hai-Xia Ma; Tie-Zheng Wei; Jin-Peng Liao; Chang-Tian Li; Zhen-Quan Yang; Yi Li (Mycology)
Cortinarius species are widely distributed in the world and constitute a diverse group of ectomycorrhizal fungi that are associated with a broad range of plant hosts. The species diversity of this genus has been investigated in China, but it remains poorly understood, especially in the subtropical region. In this study, one new section, six novel species, one new combination, one new name, and one new record of Cortinarius are reported from subtropical China based on the morphological and molecular evidences. Cortinarius lilacinicarpus, C. sinocalaisopus, C. sinosalor, C. vividus spp. nov., C. orientisalor nom. nov., and C. illibatus are typical species of the section Delibuti. Cortinarius macroflavicapus sp. nov. belongs to Macroflavicapi sect. nov., a new section in the subgenus Dermocybe. Cortinarius tianbaoyanensis sp. nov. and C. dryadicola comb. nov. belong to the section Spilomei. Detailed descriptions, basidiocarps, and microscopic photographs are provided for these species. In addition, C. leptospermorum comb. nov. in the section Pauperae and subgenus Dermocybe is proposed.